The effect of social deprivation on fragility fracture of the distal radius. Issue 6 (June 2019) - Johnson, Nick A.; Dias, JJ
Highlights: Distal radius fracture rate was higher in deprived areas. Less falls occurred in the home in deprived patients with more falls outdoors. No relationship was found between deprivation and FRAX scores. A significant relationship was identified between deprivation and increased number of falls risk factors. Abstract: Introduction: Social deprivation is associated with many adult fractures including distal radius fractures but the mechanisms for this are unclear. The aim of this study was to identify if social deprivation was associated with falls risk, mechanism of injury or osteoporosis in patients with a fragility fracture of the distal radius. Method: Details of all patients aged 50 years and over presenting with a radiographically confirmed fracture of the distal radius over a one year period, were prospectively recorded. Patients were sent a questionnaire pack including questions regarding place and mechanism of injury, comorbidity assessment, falls risk assessment tool and FRAX assessment of bone health and fracture risk. Results: 333 out of 521 eligible patients completed the questionnaire (279 female; 54 male, response rate = 64%). There was no difference between characteristics of responders and non-responders (p = 0.58). DRF rate was higher in socially deprived quintiles (p = 0.040). Less falls occurred in the home in socially deprived patients (Q1/2: 35%: Q3–5: 48%, p = 0.037) with more falls outdoors (Q1/2: 39%: Q3–5: 24%, p = 0.001). There was no difference in height from which falls took place with most occurring from standing height (Q1/2: 81%: Q3–5: 86%, p = 0.336). Linear regression analysis found no relationship between social deprivation rank and FRAX scores (major fracture risk: p = 0.274, hip fracture risk: p = 0.283) but demonstrated a significant relationship between social deprivation and increased number of falls risk factors (p = 0.002). Mean number of falls risk factors was higher in the two most socially deprived quintiles (Q1/2: 3.62: Q3–5: 2.79, p = 0.028). Conclusion: We have identified increased falls risk as an important reason for DRF in socially deprived patients. Knowing which patients are at highest risk allows interventions to be efficiently targeted. We would recommend resources should be targeted towards patients from socially deprived areas and focused on specific falls prevention strategies.